Demonstrating the applicability of Raman spectroscopy for the characterization of hydrogen loading of bicyclic liquid organic hydrogen carriers (LOHCs) under process-relevant conditions - Jander, Julius Hans; Rausch, Michael Heinrich; Wasserscheid, Peter; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2024)
During hydrogenation and dehydrogenation reactions of liquid organic hydrogen carriers (LOHC), their thermophysical properties change significantly as a function of the degree of hydrogenation (DoH). Compared with conventional techniques, Raman spectroscopy offers a contactless methodology for online process monitoring without the need of sampling. This work demonstrates the application of Raman spectroscopy for the determination of the DoH under process-relevant conditions for LOHC systems based on diphenylmethane (DPM) and benzyltoluene (BT) up to 473 K. For the DPM-based system, a previous study is extended by examining the influence of process-like disturbances. For the BT-based system, a novel approach using indirect hard modeling of the unpolarized Raman spectra is applied, which results in strongly reduced uncertainties and insensitivity towards process-like disturbances, e.g. reaction by-products. For a corresponding testing set exhibiting a pronounced fluorescent background in the Raman spectra, the DoH is determined with an average absolute deviation of 0.0057.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Benzyltoluene; Degree of hydrogenation; Diphenylmethane; Hydrogen storage; LOHC; Raman spectroscopy